The prognostic role of angiolymphatic invasion in N0 esophageal carcinoma: a meta-analysis and systematic review - Wang, An; Tan, Yulong; Zhang, Yuyan; Xu, Dong; Fang, Yuchao; Chen, Xiaofeng; Wang, Shaohua (Journal of Thoracic Disease; Vol 11, No 8 (August 31, 2019): Journal of Thoracic Disease, 2019)
Background: Angiolymphatic invasion (ALI) plays an important role in lymph node metastasis. The presence of an ALI predicts a high risk for lymph node metastasis and a poor prognosis in patients with lymph node negative esophageal carcinoma. The independent prognostic value of ALI in node-negative patients remains controversial. A meta-analysis was conducted to investigate the relationship between ALI and prognosis in cases of lymph node negative esophageal carcinoma. Methods: We searched the PubMed, EMBASE, Web of Science, and Cochrane Library databases for studies on the relationship between ALI and the prognosis of patients with esophageal carcinoma. Studies with N0 patients’ survival data related to ALI were included. The effect size (ES) was the hazard ratio (HR) with 95% confidence intervals (CI) for cancer-specific survival (CSS), overall survival (OS) and recurrence-free survival (RFS). Results: A total of 9 studies with 2,154 patients were included after applying the inclusion and exclusion criteria. The pooled HR showed that patients with ALI have a poor cancer specific survival (HR =2.54; 95% CI, 1.84–3.51; P